Hedges in Students’ Reflective Feedback: Evidence from an Online Class during COVID-19 Outbreak - Isti'anah, Arina; Puri, Anindita Dewangga (State institute of islamic studies salatiga, 2021)
Scholars have observed hedges in academic writing, yet the examination of hedges in students’ reflective feedback is scarcely found. During the Covid-19 pandemic, both teachers and students face difficulty engaging themselves in online classes. To figure out how students show their attitude, among others, is through reflective feedback. One of the language features pivotal in reflective feedback is ‘hedge’, a pragmatic feature representing a speaker’s tentativeness and possibility in communication (Lakoff, 1973). This paper addresses two questions: (1) what types of hedges are used in the students’ reflective feedback in online class during the covid-19 outbreak? and (2) what are the functions of the hedges? This paper took 151 samples of students’ reflective feedback in the introduction to English linguistics class at Sanata Dharma University to answer those problems. Findings reveal that the students dominantly used modal auxiliaries and epistemic adverbs as the types of hedges as a politeness technique to convey their anxiety and hesitation during an online class.Keywords: hedges, reflective feedback, online class